Life stressors, emotional avoidance and breast cancer - Cardenal, Violeta; Ortiz-tallo, Margarita; Martín Frías, Isabel; Martínez Lozano, Joaquina (The Spanish Journal of Psychology, 2008)
Two groups of women were assessed in psychological aspects considered by some authors of interest for personal well being. The sample consisted of 118 women, 58 diagnosed with breast cancer and 60 healthy women, of similar ages and personal circumstances. The purpose of the study was: (a) to explore the existence of stressful life events in the women’s history and their degree of subjective distress and (b) to determine whether or not there is an emotional avoidance style in the group of women with breast cancer. The following assessment instruments were employed: the “Cuestionario de Formas de Afrontamiento” (CEA), the Five-Factor Inventory NEOPI- R, and the State-Trait Anger Inventory (STAXI). The results revealed more stressful vital events in the last two years in the group of women with breast cancer and significant differences in the degree of current distress. They also obtained higher scores in current anger, resignation, and neuroticism.